Current Issues of Economic Security of the Eurasian Economic Union - Danilovna Kovaleva, Valentina; Gennadevich Rusetskiy, Mikhail; Alexandrovna Shadrina, Zhanna; Agopovna Kochyan, Gayane; Stanislavovna Zarovnaya, Larisa (International Journal of Engineering and Technology, 2018)
The article considers the main aspects that characterize the economic security system of the Eurasian Economic Union (EAEU) and means to ensure economic security that contribute to increasing economic potential and to creating conditions for the effective development of integration processes. The authors investigated the main documents of the Eurasian Economic Commission (EEC), a constantly acting regulating body of the EAEU, and developed recommendations for creating unified strategies of the economic security of the Eurasian Economic Union that can be implemented in the system of risk management that, in turn, is based on the controlling toolkit. In the process of the research it was determined that the political aspect alone is not enough for the preservation and effective development of the Eurasian Economic Union as common economic interests and possible effects from their implementation are the crucial components of viability of any integration union including the EAEU country members. In this regard the formation of the system of economic security of the integration union of Russia, Belarus, Kazakhstan, Armenia and Kyrgyzstan is a relevant issue. In order to contribute to the integration of the countries of the Eurasian Economic Union that is based on the geopolitical aspect it is necessary to ensure economic security which determines both the theoretical and practical significance of the study. At the same time such integration would promote the unification of the EAEU countries that are different in the level of their socio-economic development.Â